2017
DOI: 10.1161/hypertensionaha.117.10144
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-Visit Blood Pressure Variability in Young Adulthood and Hippocampal Volume and Integrity at Middle Age

Abstract: The aims of this study are to assess the relationships of visit-to-visit blood pressure (BP) variability in young adulthood to hippocampal volume and integrity at middle age. We used data over eight examinations spanning 25 years collected in the Coronary Artery Risk Development in Young Adults (CARDIA) Study of black and white adults (age 18–30 years) started in 1985–1986. Visit-to-visit BP variability was defined as by standard deviation (SDBP) and average real variability (ARVBP, defined as the absolute dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…Fifty-two studies ( n = 343,794, weighted mean age (MWA) = 58.7 years, women = 53.2%) met the inclusion criteria presented in Supplementary Information; Table S2 . They included 33 cross-sectional [ 5 , 6 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] and 26 longitudinal studies [ 5 , 28 , 39 , 41 , 45 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ] with follow-up ranging from ~2 [ 39 , ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifty-two studies ( n = 343,794, weighted mean age (MWA) = 58.7 years, women = 53.2%) met the inclusion criteria presented in Supplementary Information; Table S2 . They included 33 cross-sectional [ 5 , 6 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] and 26 longitudinal studies [ 5 , 28 , 39 , 41 , 45 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ] with follow-up ranging from ~2 [ 39 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-two studies reported on the peripheral BP measurement and one study additionally reported on non-invasive CPP measurement [ 60 ]. Typically, studies reported BP as a continuous measure (87.7%), but a small proportion (12.3%) reported a categorical measure (normotension vs. hypertension) [ 23 , 25 , 28 , 32 , 38 , 46 , 54 , 69 ] Several methods were used to assess BP including occasional BP (78.8%), 24-h ambulatory BP monitoring (ABP, 11.5%) [ 21 , 39 , 56 , 61 , 66 , 67 ], BP variability over different visits (9.6%) [ 26 , 57 , 62 , 63 ], BP during exercise (2%) [ 58 ], BP reactivity in response to stress (2%) [ 34 ], and inter-arm differences in SBP (2%) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A line of research in neurology and cardiology suggests that the intra-individual variability across successive blood pressure readings may be important to neurological outcomes of incident and recurrent stroke or transient ischemic attack [ 11 14 ]. However, the magnitude of association between such blood pressure fluctuation, known as blood pressure variability (BPV), and other neurological outcomes remains less clear [ 15 17 ]. Though incompletely understood, high BPV potentially leads to carotid artery denervation and endothelial damage reducing perfusion in microvascular vessels [ 18 ].…”
Section: Introductionmentioning
confidence: 99%